2017
DOI: 10.3389/fimmu.2017.01505
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Administration of Betamethasone Causes Changes in the T Cell Receptor Repertoire Influencing Development of Autoimmunity

Abstract: Prenatal glucocorticoids are routinely administered to pregnant women at risk of preterm delivery in order to improve survival of the newborn. However, in half of the cases, birth occurs outside the beneficial period for lung development. Glucocorticoids are potent immune modulators and cause apoptotic death of immature T cells, and we have previously shown that prenatal betamethasone treatment at doses eliciting lung maturation induce profound thymocyte apoptosis in the offspring. Here, we asked if there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 85 publications
(96 reference statements)
0
16
0
Order By: Relevance
“…route, and lymphocyte suppression was also comparable for the BetaP plus BetaA. A concern for clinical use is that corticosteroids have large effects on the developing immune system of the fetus that could alter immune function in the child and adult …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…route, and lymphocyte suppression was also comparable for the BetaP plus BetaA. A concern for clinical use is that corticosteroids have large effects on the developing immune system of the fetus that could alter immune function in the child and adult …”
Section: Discussionmentioning
confidence: 87%
“…A concern for clinical use is that corticosteroids have large effects on the developing immune system of the fetus that could alter immune function in the child and adult. [33][34][35] The study has limitations as we studied only fasted healthy Indian-Asian women. Extrapolation to other populations of different racial backgrounds, a wide range of BMI, nonfasted, and pregnant women must be done with caution.…”
Section: Discussionmentioning
confidence: 99%
“…A mouse study showed significant reduction in thymic size and cell numbers after prenatal betamethasone in the three mouse strains tested (Gieras et al, ). Only in the lupus‐prone MRL/lpr strain, did prenatal glucocorticoids induce changes in the T cell repertoire (CD4 + , CD8 + , and CD4 − CD8 − ) that resulted in increased numbers of autoreactive T cells (Gieras et al, ). Similarly, a study performed in rats demonstrated that prenatal dexamethasone, another glucocorticoid, exposure increases the susceptibility to autoimmunity, namely, experimental autoimmune encephalomyelitis (EAE) and adjuvant‐induced arthritis (AIA) in offspring (Sun et al, ).…”
Section: Autoimmunitymentioning
confidence: 99%
“…Although a previously discussed study associated the glucocorticoid dexamethasone with immunosuppression (Coe & Lubach, 2000), other studies have found a connection between prenatal glucocorticoid exposure and autoimmunity. A mouse study showed significant reduction in thymic size and cell numbers after prenatal betamethasone in the three mouse strains tested (Gieras et al, 2017). Only in the lupus-prone MRL/lpr strain, did prenatal glucocorticoids induce changes in the T cell repertoire (CD4 + , CD8 + , and CD4 − CD8 − ) that resulted in increased numbers of autoreactive T cells (Gieras et al, 2017).…”
Section: Autoimmunitymentioning
confidence: 99%
“…However, studies regarding the effects of prenatal GCs on the development of autoimmunity are limited. Recently, using a mice model, Tolosa and colleagues demonstrated that prenatal administration of betamethasone increases apoptosis of developing thymocytes and induces changes in the TCR repertoire decreasing the frequency of pathogenic T cells and protecting from T1D development in NOD mice ( 184 , 185 ). Conversely, an epidemiological study in Danish cohorts indicated the existence of an increased risk for T1D and T2D in young children who received prenatal steroid treatment ( 186 ).…”
Section: Hormones Neuropeptides and Neurotransmitters Modulate T Cementioning
confidence: 99%